What do the together or apart journeys of siblings in care look like? A sequence analysis of sibling placement trajectories. - Schmits, Florie; Wijedasa, Dinithi (International Journal of Population Data Science, 2025)
Objective This presentation offers a longitudinal perspective on sibling placement trajectories of children in care, with the aim of creating distinct typologies of sibling placement journeys. The presentation will also show the potential for social sequence analysis to generate policy and practice relevant knowledge on the trajectories of children in care. Methods Research studying sibling separation often regards separation as a one-point-in-time issue, which does not capture the complexity and heterogeneity of siblings' placement journeys in care. This study follows a cohort of 360 children from two local authorities in England, and uses their historical placement data to show their living situations with or without siblings during their time in care. It uses sequence analysis as the method to consider the timing, duration and sequence of sibling placements of the children over time. Results This presentation will highlight emerging results from our research on sibling placement trajectories using sequence analysis. Results will highlight the different sibling placement states each child experienced (placed with all, some of no siblings), the time children spent in those states and the transitions they experienced. The longitudinal characteristics of individual trajectories and the similarity between the sequences of the cohort children will be discussed. The cluster analysis and regression analysis results will help us understand how child, sibling group and placement characteristics are associated with experiencing a particular sibling placement trajectory (cluster membership). Conclusion Results will be summarised by exploring the distinct typologies of sibling placement journeys that were found, considering the policy and practice implications and discussing how these results could be used for further research into the effect of togetherness journeys on outcomes.